Student Employment during College Studies and After Career Start - Mikhail Vasilievich Vinichenko; Sergey Anatolyevich Makushkin; Alexander Vasilievich Melnichuk; Elena Victorovna Frolova; Svetlana Nikolaevna Kurbakova (International Review of Management and Marketing, 2016)
The present research paper is targeted at exploring problems of students’ and graduates’ entering the labor market, exploiting their labor and creative potential during employment in their area of expertise, as well as their ability to combine university’s studies with labor activities and vise versa. The article deals with some demographic aspects challenging graduates. Besides the authors are seeking to research tendencies in employment of students and graduates under the conditions when one crisis follows the other and their attitude to further professional career development. General scientific methods and tools, including UK Higher Education Statistics Agency's ones, have been used in complex to achieve the above mentioned goals.